Basic Terminology of Landscaping: Sources and Contemporary Condition - O. Taranov, Alexey; N. Taranova, Elena; A. Kolesnikova, Ksenia; I. Belousova, Lyudmila; N. Furmanova, Tatiana (International Journal of Engineering and Technology, 2018)
The problem of interpreting and changing the meaning of terms is relevant in many sciences, including in linguistics. The authors touch on the problem of different interpretations of basic terms in the landscape studies. The article deals with the history of the origin of the terminological vocabulary of the landscape science, describes the problems associated with its use by specialists and the changing meanings of terms over the past decades. Whereas these terms are mostly used interchangeably, there are obviously some fine differences in meaning. In this paper, important moments of the scientific understanding of the basic terms of landscape are presented.Â